2023
DOI: 10.2478/aoas-2022-0093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carcass lesions and their effects on welfare, carcass composition and meat quality in slaughtered pigs

Abstract: The aims of this study were to determine the prevalence of carcass lesions in slaughtered pigs and to quantify their relationships with different animal characteristics, pre-slaughter factors, blood measurements, performance indices, carcass composition and meat quality traits. Data was recorded for 30 journeys referring to 1080 market-weight pigs that originated from 15 commercial small-scale finishing farms. Carcass lesions were visually assessed on the slaughterline in different parts of the carcass, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
1
0
1
Order By: Relevance
“…A recent study reported a higher proportion of severe carcass lesions in heavierweight pigs (133 vs. 85 kg on average; [66]), whereas similar to our studies, Rocha et al [10] failed to find differences in skin bruise scores between pigs of two different slaughter weights, although the groups only differed by 13 kg in their study. The discrepancy in the results between studies may be thus explained by the body weight difference between tested groups.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study reported a higher proportion of severe carcass lesions in heavierweight pigs (133 vs. 85 kg on average; [66]), whereas similar to our studies, Rocha et al [10] failed to find differences in skin bruise scores between pigs of two different slaughter weights, although the groups only differed by 13 kg in their study. The discrepancy in the results between studies may be thus explained by the body weight difference between tested groups.…”
Section: Discussionsupporting
confidence: 78%
“…However, they did not evaluate lesion severity and provided no detailed description of how lesions were observed (distance, minimum lesion size), and therefore, the comparison must be interpreted with extreme caution. With respect to lesions on the carcasses, similarly to the present study, Čobanović et al [ 33 ] assessed lesions at slaughter in heavy pigs (121–145 kg BW) using the Welfare Quality ® classification [ 17 ], and they found moderate carcass lesions (5–10 lesions on the body) in 26% and severe lesions (more than 15) in 55% of slaughtered pigs. In the present study, regardless of the experimental group and based on the visible areas, we observed 20% of moderately damaged carcasses and 5% of severely damaged carcasses (data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, evaluating the stress in livestock through the appropriate indicators and eliminating factors that cause stress-induced responses . The important issue is how these situations influence products and their acceptability, as poor welfare led to some important defects such as the death of animals, body weight loss, carcass lesions and composition, and meat quality defects, i.e., pale, soft, exudative (PSE) and dark, firm, dry (DFD) meats (Čobanović et al, 2019;Čobanović et al, 2021;Čobanović et al, 2023;Karabasil et al, 2017;Urrea et al, 2021;Vicic et al, 2021;Zappaterra et al, 2022). According to (Čobanović et al, 2023), carcass lesions (severe, moderate or low) are connected with alterations in blood measurements in slaughtered pigs and compromised animal welfare, affected by both animal characteristics and pre-slaughter conditions.…”
Section: Welfarementioning
confidence: 99%
“…As pointed out by the same authors, the presence of carcass lesions, severe or moderate, led to the alterations in meat quality with the higher occurrence of DFD or PSE meat and consequently to economic and financial losses. Good communication between stakeholders (slaughterhouses, transporters, and farmers), providing feedback of information among others, e.g., results of carcass lesions in slaughtered pigs from abattoir to previous steps in the meat chain could contribute to identifying critical points and eliminating negative factors with improved animal welfare in each phase (Čobanović et al, 2021;Čobanović et al, 2023;Karabasil et al, 2017). The application of regular, educational and training programs (animal behaviour, good management practice, standard operating procedure) to train operators (on the farm, during transport, at slaughterhouse) for prudent management of livestock is of great importance for good practice and proper handling (Čobanović et al, 2023;Kjosevski et al, 2021;Zappaterra et al, 2022).…”
Section: Welfarementioning
confidence: 99%
See 1 more Smart Citation